The Nanoporous RP-20 Carbon Electrode as a Model for Energy Storage and Conversion Systems – Studied with µCT, SAXS and SANS Techniques. (7th July 2017) - Härk, Eneli; Kardjilov, Nikolay; Hilger, André; Petzold, Albrecht; Risse, Sebastian; Vaas, Ingrid; Goerigk, Günther; Jafta, Charl; Ballauff, Matthias; Lust, Enn
Abstract : The manuscript describes quantitative morphological and structural information for the nanoporous RP-20 powder andelectrode based on that carbon - studied with X-ray microcomputed tomography, small-angle neutron scattering, and small-angle X-ray scattering techniques. μCT measurements demonstrated that the diffusion process inside of the RP-20 electrode is significantly influenced by the nature of the solvent. SAXS measurements were performed in order to collect quantitative morphological and structural information for nanoporous RP-20 powder-polytetrafluoroethylene binder based electrode material. Comparison of the complementary scattering techniques, i.e., SAXS and SANS has been provided. The interaction of heavy water inside of the nanoporous PR-20 based electrode by SANS technique was observed.